Medición inalámbrica de concentración de oxígeno para productos vitivinícolas - Garzon Rey, Jorge Mario; Osma, Johann F.; Segura-Quijano, Fredy (Ingeniería, 2012)
This paper presents a wireless system for measuring the oxygen concentration suitable for bottled wine. The architecture system is based on wireless powering and inductive telemetry data communication eases the information about wine quality via an oxygen sensor inside the bottle. A high level of oxygen show salow quality of bottled wine. A bad sealing process and corks defects increase the oxygen concentration. The proposed system was validated using adiscrete component implementation available on local market. The given architecture was designed in to a ASIC future application. The prototype use a commercial Alphasense A2O2 oxygen sensor, the implemented system shows ahigh linea rresponse with a correlation coefficient of 0.999.